Mindfulness Training for Primary Care for Portuguese-Speaking Immigrants: A Pilot Study - Trombka, Marcelo; Creedon, Timothy B.; Demarzo, Marcelo; Cuoco, Letícia T.; Smith, Lydia; Oxnard, Alexandra C.; Rozembaque, Alana T.; Hirayama, Marcio S.; Moreno, Natalia B.; Comeau, Alexandra; Gawande, Richa; Griswold, Todd; et al. (Frontiers in Psychiatry, 2021)
Background: Portuguese-speaking immigrants are a growing underserved population in the Unites States who experience high levels of psychological distress and increased vulnerability to mental health disorders such as depression and anxiety. Current evidence shows that mindfulness-based interventions (MBIs) are effective to promote physical and mental health among educated English speakers; nonetheless, the lack of diversity in the mindfulness literature is a considerable limitation. To our knowledge, the feasibility and acceptability of MBIs among Portuguese-speaking immigrants have not yet been investigated. Methods: This single-arm pilot study (N = 30) explored the feasibility, acceptability, and cultural aspects of Mindfulness Training for Primary Care (MTPC)-Portuguese among Portuguese-speaking immigrants in the Boston area. MTPC is an 8-week, primary care-adapted, referral-based, insurance-reimbursable, trauma-informed MBI that is fully integrated into a healthcare system. The study also examined intervention preliminary effectiveness on mental health outcomes (depression and anxiety symptoms) and self-regulation (emotional regulation, mindfulness, self-compassion, interoceptive awareness), and initiation of health behavior was explored. Results: Primary care providers referred 129 patients from 2018 to 2020. Main DSM-5 primary diagnoses were depression (76.3%) and anxiety disorders (6.7%). Participants (N = 30) attended a mean of 6.1 (SD 1.92) sessions and reported a mean of 213.7 (SD = 124.3) min of practice per week. All survey finishers would recommend the program to a friend, found the program helpful, and rated the overall program as “very good” or “excellent,” and 93% would participate again, with satisfaction mean scores between 4.6 and 5 (Likert scale 0–5). Participants and group leaders provided feedback to refine MTPC-Portuguese culturally responsiveness regarding materials language, settings, time, food, and community building. Patients exhibited reductions in depression (d = 0.67; p < 0.001) and anxiety (d = 0.48; p = 0.011) symptoms, as well as enhanced emotional regulation (d = 0.45; p = 0.009), and among survey finishers, 50% initiated health behavior change through action plan initiation. Conclusion: This pilot study suggests that MTPC-Portuguese is feasible, acceptable, and culturally appropriate among Portuguese-speaking patients in the Boston area. Furthermore, the intervention might potentially decrease depression and anxiety symptoms, facilitate health behavior change, and improve emotional regulation. MTPC-Portuguese investigation with larger samples in controlled studies is warranted to support its dissemination and implementation in the healthcare system. Clinical Trial Registration: Identifier: NCT04268355.